CLINICAL TERMINOLOGY. WORD FORMATION, GREEK ROOTS, SUFFIXES AND PREFIXES (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
In the world of healthcare and medicine, we often encounter a seemingly impenetrable web of complex, multisyllabic words and phrases that can leave even the most attentive readers and listeners baffled. This jargon, commonly referred to as clinical terminology, plays a pivotal role in accurate medical communication and the conveyance of crucial medical information. To gain a better understanding and the ability to decode this seemingly cryptic language, it's important to explore the intricacies of word formation, particularly the influence of Greek roots, suffixes, and prefixes.